Military communities in late medieval England essays in honour of Andrew Ayton - Baker, Gary P. ca. 20./21. Jh; Lambert, Craig ca. 20./21. Jh; Simpkin, David ca. 20./21. Jh (Warfare in history, 2018)
The theme of warfare as a collective enterprise investigated in the theatres of both land and sea